Optimal decay estimates for solutions to damped second order ODE’s - Bárta Tomáš (Electronic journal of qualitative theory of differential equations, 2018)
In this paper we derive optimal decay estimates for solutions to second order ordinary differential equations with weak damping. The main assumptions are Kurdyka–Łojasiewicz gradient inequality and its inverse.